(untitled) (Lex localis - Journal of Local Self-Government, 2025)
Despite the national law and UNESCO guidelines, Jordan is currently in the early stages of AI-enabled special education (UNESCO, 2025). The paper focuses on the prospects and pitfalls regarding the acceptance of ’AI-integrated disability technologies’ in Jordan. Therefore, the technology acceptance model (TAM) was applied as a theoretical framework, suggesting how an individual’s discretion influences the acceptance of specific technology(Schorr, 2023). Furthermore, the study engages with epistemology and ontology research paradigms to determine both subjective and deductive logical reasoning (Al-Ababneh, 2020). A mixed-method survey of 300 respondents encompassing "teachers, administrators, and policymakers" was employed as a data collection instrument. Open-ended questions were "explored" through qualitative ’thematic analysis’, whereas closed-ended questions were "examined" through quantitative ’sampling techniques. Regression findings with a low (R²= 0.009) highlight that large-scale acceptance of AI-driven special education in Jordan faces key challenges, including cultural barriers, limited tech infrastructure, and insufficient qualified personnel.